Welfare versus work under a negative income tax: Evidence from the Gary, Seattle, Denver and Manitoba income maintenance experiments - Chris Riddell; William Craig Riddell (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2021)
The Income Maintenance Experiments have received renewed attention due to growing international interest in a Basic Income. Proponents viewed a Negative Income Tax as a replacement for traditional welfare with stronger work incentives and reduced poverty. However, existing labor supply estimates for single parents are uniformly negative. We reassess the experimental evidence and find randomization failure in two NITs (Gary and Seattle). In Denver and Manitoba, we find a positive labor supply response for those on welfare prior to random assignment. Our results provide strong evidence that a NIT can increase work activity among single parents on welfare.
Keywords: C9; I38; J22; 330